The Degree of Application of Sixth Grade Teachers of Reflective Thinking Skills in the Subject of Social Studies, a Field Study in the City of Lattakia - أحمد, رفيف; ميساء حمدان (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aims to know the degree to which social studies teachers of the sixth grade apply reflective thinking skills in basic education schools in the city of Lattakia, and to achieve the objectives of the research, the descriptive method was used, a questionnaire was prepared for reflective thinking skills, and the study sample consisted of (62) male and female teachers for the academic year 2021- 2022, the researcher reached to the following results That the teacher’s application of reflective thinking skills come to a medium degree in general. There are differences in the teacher’s application of reflective thinking skills, where the skill of reaching conclusions came to a high degree, while the teacher’s application of the skills of reflection and observation, and the detection of in accuracies came to a medium degree, while the teacher’s application of skills and suggested solutions came to a low degree. Encouraging teachers to use reflective thinking skills in the educational process, and urging learners to apply them. Attention to preparing teachers with a high ability of knowledge and awareness in the use of reflective thinking skills.